Dùndún Drumming in Yorubaland - Kayode., S. (Journal of Performing Arts:University of Ghana, Legon, 2012)
The dùndún, a double-headed hourglass tension drum s the most popular and widely performed of all Yorùbá drums used for both religious and social ceremonies. This paper examines the place of dùndún music in Yoruba culture. Using in-depth interviews (IDI) and participant-observation methods, a collection of data aided by an audio tape recorder and digital/still camera was embarked upon during a fieldwork carried out in selected prominent Yoruba communities. The mode of skill acquisition on dùndún is based on the social learning theory, since the learner follows set examples of a model through an apprenticeship system. The paper, thereafter, advocates for the utilization of the effective traditional system of education in teaching music in Africa‟s institutions of learning due to its potentials for making music learning more culturally relevant to students at different levels.